Дослідження гідравлічних характеристик відцентрових форсунок градирень і шляхи їх покращання - Dubrovskyi V.V.; Pidvysotskyi O.M. (General Energy Institute of the National Academy of Sciences of Ukraine, 2008)
We have carried out an experimental investigation of the hydraulic characteristics of centrifugal atomizers of cooling towers. We analyzed the data obtained and found empirical generalizing dependencies for the coefficient of hydraulic resistance and coefficient of discharge.